A Comparative Study Between Laparoscopic Management of Ectopic Pregnancy and Laparotomy: Experience in Tertiary Care Hospital in Bangladesh: A Prospective Trial - Jahan, Samsad; Das, Tripti Rani; Habib, Samira Humaira; Jahan, Akter; Joarder, Mahjabin; Nahar, Nurun; Banarjee, Manisha (Bangladesh Journal of Endosurgery, 2014)
Objectives: To compare the efficiency and surgical morbidity associated with laparoscopic management of tubal ectopic pregnancy (EP) compared with that of open laparotomy. Materials and methods: During November 2008 to October 2012, there were 89 with a confirmed ectopic pregnancy These patients were admitted through emergency or outpatient department and managed by laparoscopy (number 70) and by laparotomy (number 19). The diagnosis of ectopic pregnancy was based on history, clinical symptoms, physical examination, a positive serum B-human chorionic gonadotropin (B-HCG), transvaginal ultrasonography. Patients were informed pre-operatively about the surgical procedures. The main outcome measured included operative time, blood loss, and complications. Results: Laparoscopic surgery gives an overall success rate of 98.9%. Linear salpingostomy was the main procedure performed in both groups. Estimated blood loss was significantly lower in the laparoscopy group compared with laparotomy group (p<0.001). Only 3 (3.81%) patients in the laparoscopy group required blood transfusion, whereas 16 (74.94%) in the laparotomy group needed transfusion (P<0.0001). The duration of operation in laparoscopy group was 53.2 ± 16.8 minutes and 84.5 ± 30.3 minutes in the laparotomy group. The duration of hospitalization was significantly shorter in the laparoscopy group 1.12±0.5 days compared to 5.25±0.1days in the laparotomy group (p<0.0001). ). In the laparoscopy group 57(72.4%) patients did not need analgesia after surgery compared with laparotomy group where all the patients needed analgesia. Conclusion: Laparoscopic treatment (Salpingostomy or Salpingectomy) of EPs offers major benefits superior to laparotomy in terms of less blood loss, less need for blood transfusion and postoperative analgesia, a shorter duration of hospital stay. Laparoscopic management of ectopic pregnancy might be the most beneficial procedure with maximal safety and efficacy.